Report of the Working Group on Skill Development and Training for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, 2001)
To review the on going programmes for skill development under different streams like craftsmen and vocational training including non-formal training system, and skill development efforts in the unorganized sector and assess their relevance in the context of technological change taking place in the economy as also objectives like productivity and incomes, specially in the unorganized sector of the economy; To identify emerging requirements of training, both formal and non-formal; To assess the capacity and potential of existing institutional set up both in public and private sector in relation to the emerging skills requirements, both in quantitative and qualitative terms. To recommend suitable strategies and mechanisms for achieving a better matching of demand and supply of skills in the medium term.
Government of India, Planning Commission